2011
DOI: 10.2478/v10120-011-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of phenols in the influence of herbal extracts from Salvia officinalis L. and Matricaria chamomilla L. on two-spotted spider mite Tetranychus urticae Koch

Abstract: Extracts prepared from 2 medicinal herbs (common sage Salvia officinalis L. and German chamomile Matricaria chamomilla L.) were used in this study for biological control of spider mites. Their effect on mortality, fecundity, and development of Tetranychus urticae Koch on English ivy (Hedera helix L.) was studied under laboratory and greenhouse conditions. The extracts were prepared by soaking fresh Salvia leaves or dry Matricaria flowers in ethanol for 24 h, followed by evaporation, and finally suspension of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
(22 reference statements)
1
9
0
Order By: Relevance
“…They are toxic towards spider mites which live on the undersides of leafs and plants [70] and they are reported to cause toxicity towards soil fauna in general [18]. This is further underlined by the fact that phenolic compounds can serve as defense substances of plants against herbivore attack [71].…”
Section: Hypothesis Iii: Interplay Between Stress Factorsmentioning
confidence: 98%
“…They are toxic towards spider mites which live on the undersides of leafs and plants [70] and they are reported to cause toxicity towards soil fauna in general [18]. This is further underlined by the fact that phenolic compounds can serve as defense substances of plants against herbivore attack [71].…”
Section: Hypothesis Iii: Interplay Between Stress Factorsmentioning
confidence: 98%
“…Regarding SoLEEtOH70% , our results was in agreements with Mohamed et al (2015) who found that the ethyel acetate of S. officinalis extract reduced the total number of T. urticae eggs. Similarly, Tomczyk and Suszko (2011) found that the ethanolic leaf extract of S. officinalis diminished T. urticae female's fecundity.…”
Section: Assessment Of the Egg-laying Capacity Of T Urticae Adult Femalesmentioning
confidence: 90%
“…This also was in accordance with Waked (2016) who recorded 35% of egg mortality when treated with both the methanolic and aqueous leaf extracts of S. officinalis (20%). In contradiction, Tomczyk and Suszko (2011) recorded the low ovicidal effect of the ethanolic leaf extract of S. officinalis against T. urticae eggs.…”
Section: Direct Toxicity To T Urticae Zero-time Eggsmentioning
confidence: 98%
See 1 more Smart Citation
“…(Asclepiadecae), Nerium oleander L. (Apocynacae) (Islam et al, 2008), were reported as botanical acaricides (Derbalah et al, 2013). They contain secondary metabolites known from their repellent, antifeedant, ovicidal and killing action against arthropod pests (Smith, 1989;Tomczyk & Suszko, 2011).…”
Section: Introductionmentioning
confidence: 99%